Romanization problems within the language policy of the Republic of Kazakhstan (Journal of Philosophy Culture and Political Science, 2018)
The article develops the political aspects of the language policy, which meets demands of the multiethnic population of the country, and takes account of the language, demographic and political situation in the Republic of Kazakhstan. The work analyses the establishment of Kazakh as the state language, and substantiates the advantages of the strategy of state policy in terms of preserving and functional developing of the languages during the transitional period, and explores the priority directions of the language development in the context of changing the script to Latin alphabet. Key words: language politics, latinizing, assimilation, consolidation.